Best Proximity Point Results in Generalized Metric Spaces: Naeem Saleem, Mujahid Abbas, Sadia Farooq - Team, Support (Thai Journal of Mathematics, 2022)
In this paper we define a new class ofmappings called (θ ,α ^+)- proximal admissible contractionsand obtain a unique best proximity point for such mappings in the setting ofcomplete generalized metric space. Our result is an extension of comparableresults in the existing literature. Some examples are presented to supportthe results proved herein